근로자 절주 프로그램의 효과 - 김금이(Keum Ee Kim) (지역사회간호학회지, 2007)
Purpose: To evaluate a reducing alcohol intervention program for workers. Method: The intervention program employed one-group pretest-post-test design with repeated measuring by quasi-experimental study. The program was developed from literature review based on the Transtheoretical Model, and evaluated from April 6 to June 22, 2006. Sixteen white collar male workers participated. At the beginning, the subjects were at the pre-contemplation stage (50%) and contemplation stage (50%). The intervention was applied personally or in group twice a week for 9 weeks. Results: The scores of each stage of change in the post-test increased significantly compared with those in the pretest. The scores of process (cognitive and behavioral) of change in the post-test increased significantly compared with those in the pretest. The score of self-efficacy of change in the post-test increased significantly compared with that in the pretest. The score of pros-cons for drinking in the post-test decreased significantly compared with that in the pretest. The consumption of alcohol a week and a day in the post-test decreased significantly compared with that in the pretest. The levels in ALT, AST, GGT, total cholesterol, triglyceride, B.P. and BMI in the post-test did not decrease significantly compared with those in the pretest, but the level of FBS decreased significantly compared with that in the pretest. Conclusion: The above result informs us that a stage-based reducing alcohol intervention program for workers has the effect of increasing the stages of change, the process of change (cognitive and behavioral) and self-efficacy, and decreasing pros-cons for drinking alcohol consumption and FBS, and it also has a value as an effective means of nursing for workers.